2017
DOI: 10.1111/lre.12199
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton as biomonitors: A study of Museum Lake in Government Botanical Garden and Museum, Thiruvananthapuram, Kerala India

Abstract: An assessment of the pollution status of Museum Lake in the Thiruvananthapuram Botanical Garden and Museum was conducted. Analysis of different community structures of the planktonic taxa in the lake revealed it is organically polluted, attributable to the organic litter from riparian vegetation. A total of 30 most pollution‐tolerant phytoplankton genera and 24 pollution‐tolerant species were identified. Pollution‐tolerant phytoplankton genera in the lake included Chlorophyceae, Bacillariophyceae, Cyanophyceae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Investigator worldwide have examined various water bodies using pollution tolerant diatom species to measure the pollution level by employing algal indices such as Palmer’s Algal Index; Chlorophycean Index; Nygaard’s phytoplankton indices to better realize the water quality. For example, some investigator utilized Nygaard’s Algal Index to evaluate the trophic status of Hatia Dam revealing the oligotrophic condition of water bodies [ 30 ]. Mishra and co-workers studied the Bhoj Wetland, employing Nygaard’s Algal Index to illustrate the wetland’s eutrophic nature [ 31 ].…”
Section: Ecological Significance Of Diatomsmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigator worldwide have examined various water bodies using pollution tolerant diatom species to measure the pollution level by employing algal indices such as Palmer’s Algal Index; Chlorophycean Index; Nygaard’s phytoplankton indices to better realize the water quality. For example, some investigator utilized Nygaard’s Algal Index to evaluate the trophic status of Hatia Dam revealing the oligotrophic condition of water bodies [ 30 ]. Mishra and co-workers studied the Bhoj Wetland, employing Nygaard’s Algal Index to illustrate the wetland’s eutrophic nature [ 31 ].…”
Section: Ecological Significance Of Diatomsmentioning
confidence: 99%
“…Sharan and Rekha used Nygaard’s Algal Index in their evaluation of the trophic status of Hatia Dam, finding the waterbody to exhibit an oligotrophic status [ 33 ]. But still, diatoms potential is hardly exploited as bioindicators in determining the economic conditions as compared to other groups of microalgae [ 30 ].…”
Section: Ecological Significance Of Diatomsmentioning
confidence: 99%
“…Physicochemical parameters are an important factor in determining the abundance of phytoplankton and indicating the status of water quality in an aquatic ecosystem. Ajayan and Ajit Kumar (2017) suggested that phytoplankton diversity and abundance effectively monitor deteriorating water conditions. On the other hand, water quality parameters such as temperature, pH, salinity and dissolved oxygen regulate the species composition of phytoplankton (El Gammal et al, 2017).…”
Section: Phytoplankton Assemblages In Relation To Physicochemical Par...mentioning
confidence: 99%
“…On the other hand, some of the phytoplankton genera and species found throughout the sampling period, such as Cyclotella meneghiniana, Coelastrum sp., Closterium sp., Gomphonema sp., Scenedesmus sp., Nitzchia sp., Navicula sp., Euglena sp., Phacus sp., Pediastrum sp., Synedra ulna., and Tracheolomonas sp., were significant species used to indicate the conditions of the Pinang River due to their characteristics as a pollutant-tolerant species (Ajayan & Ajit Kumar, 2017). Other than Coelastrum sp.…”
Section: Phytoplankton Communities In Pinang River Malaysiamentioning
confidence: 99%
“…PPI: This index has been considered by many scientists as an effective tool to evaluate the level of organic pollution in aquatic environment (Ajayan, Ajit Kumar, 2018;Cicek, Amuc, 2017;Ghaderpoori et al, 2018;Kar et al, 2018;Vishal, Metta, 2020;Yusuf, 2020). The rating of water quality indices is based on the occurrence of pollution indicator species in the sampled water bodies.…”
Section: Determination Of Water Qualitymentioning
confidence: 99%